Fcc nanostructured TiFeCoNi alloy with multi-scale grains and enhanced plasticity. (15th January 2018) - Fu, Zhiqiang; MacDonald, Benjamin E.; Zhang, Dalong; Wu, Bingyong; Chen, Weiping; Ivanisenko, Julia; Hahn, Horst; Lavernia, Enrique J.
Abstract: Face-centered cubic (fcc) nanostructured high entropy alloys (HEAs) are characterized by high strength and low plasticity. The objective of the present study was to investigate the question of whether it is possible to increase plasticity while retaining strength in a medium-entropy TiFeCoNi alloy by promoting the formation of a multi-scale microstructure. To accomplish this objective we synthesized a bulk Ti10 Fe30 Co30 Ni30 medium-entropy alloy (MEA) via mechanical alloying (MA) and spark plasma sintering (SPS). This synthesis approach yielded a multi-scale microstructure consisting of distinctly coarse grains (> 1 μm) and nanosized grains. The mechanisms responsible for the associated mechanical behavior are discussed. Graphical abstract: Image 2